National Federation of Women Teachers, 1906 (1906)
1906 1880-1914 "National Federation of Women Teachers, 1906" [EP0056], 1906 Founded in 1904 as the Equal Pay League, it was re-named in 1906 as the National Federation of Women Teachers. Most of its members were also members of the National Union of Teachers or the London Mistresses Association and its objectives were equal pay and increased representation of women in the NUT. In 1909, the London section of the NFWT broke away from the NUT and together with the Women Teachers Franchise Union formed the Union of Women Teachers, the aim being women's suffrage and equal pay. In 1920, the remaining NFWT members also left the NUT to form an independent union, the National Union of Women Teachers. In 1961, when equal pay had been achieved, the Union wound up. These letters in the Schoolmistress for 31 October, 1907 outline the NFWT criticisms of the NUT.